Chiral signs of TPPS co-assemblies with chiral gelators: role of molecular and supramolecular chirality. Issue 84 (30th September 2016) - Wang, Qiuling; Zhang, Li; Yang, Dong; Li, Tiesheng; Liu, Minghua
Abstract : The chirality of TPPS J aggregates followed the supramolecular chirality of assemblies from chiral molecules rather than the molecular chirality. Abstract : A dianionic tetrakis(4-sulfonatophenyl)porphyrin (TPPS) self-assembled into J-aggregates when it co-assembled with a chiral cationic amphiphile via supramolecular gelation. The chiral signs of TPPS J aggregates followed the supramolecular chirality of amphiphilic assemblies rather than the molecular chirality of the amphiphile.